Antibacterial activity of ethanolic leaf extract of Aquilaria malaccensis against multi-drug-resistant Gram-negative pathogen - Jihadi, N. I. M.; Hashim, Yumi Zuhanis Has-Yun; Ab Rahim, Nurhidayah; Kamal, K.M.; Mohd Noor, Najihah; Abdullah Sani, Muhamad Shirwan; Mahamad Maifiah, Mohd Hafidz (Rynnye Lyan Resources, 2020)
The rapid emergence of resistant Gram-negative bacteria and the limited discovery of novel antibiotic is a global healthcare challenge. Many medicinal plants with potent bioactivities have been developed for the treatment of bacterial infections. Aquilaria malaccensis exhibits wide applications from perfumes and aromatic foods ingredients and great potential in medicines. In this study, crude leaf extract of A. malaccensis was evaluated for its antibacterial activity against several pathogenic Gram-negative bacteria. The leaves were processed and extracted by Soxhlet method using ethanol as the solvent. The antibacterial activity of the crude extract was tested by disc diffusion method, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against Acinetobacter baumannii (ATCC 19606), Klebsiella pneumoniae (ATCC 10031 and ATCC 700603) and Escherichia coli (ATCC 1129). Using the optimized method, the Soxhlet extract produced a yield of 178.41 mg/g. Treatment of the extract at 200 mg/mL displayed the largest inhibition zones of 14.0 mm and 9.7 mm against A. baumannii and K. pneumoniae ATCC 10031, respectively. In contrast, against E. coli and K. pneumoniae ATCC 700603, smaller zones of inhibitions of 3.3 mm were demonstrated. The MIC values of the extract were 32 mg/mL against A. baumannii and K. pneumoniae ATCC 10031 and 64 mg/mL against E. coli and K. pneumoniae ATCC 700603. The MBC values of the extract were consistent with the MIC values for all the bacteria investigated. Overall, this study was the first to show antibacterial activity of A. malaccensis leaves extract particularly against A. baumannii and K. pneumoniae and potentially develop for the treatment of resistant bacteria.